Potential screening indicators for early diagnosis of NAFLD/MAFLD and liver fibrosis: Triglyceride glucose index–related parameters - Xue, Yan; Xu, Jiahui; Li, Man; Gao, Yueqiu (Frontiers in Endocrinology, 2022)
Importance: HOMA-IR and TyG index-related parameters (TyG index, TyG-WC, TyG-WHtR and TyG-BMI) are gradually considered as convenient and alternative indicators for insulin resistance in various metabolic diseases, but the specific diagnostic capacity and the comparison of the parameters in Nonalcoholic fatty liver disease (NAFLD), Metabolic associated fatty liver disease (MAFLD) and liver fibrosis remain uncertain. Objective: To comprehensively assess and compare the diagnostic accuracy of the above parameters in NAFLD, MAFLD and liver fibrosis and identify the appropriate indicators. Methods: 1727 adults were enrolled from the 2017-2018 National Health and Nutrition Examination Surveys. Logistic regressions were used to identify the parameters significantly associated with NAFLD, MAFLD and liver fibrosis; receiver operating characteristic curves to evaluate and compare their diagnostic capacity. Subgroups analyses were conducted to validate the concordance, and the optimal cut-off values were determined according to the Youden indexes. Results: Significant differences were observed between quartile-stratified HOMA-IR and TyG index-related parameters across the NAFLD, MAFLD and liver fibrosis (P < 0.05). All variables were significantly predictive of different disease states (P < 0.05). The top three AUC values are TyG-WC, TyG-WHtR and TyG-BMI, with AUCs of 0.815, 0.809 and 0.804 in NAFLD. The optimal cut-off values were 822.34, 4.94 and 237.77, respectively. Similar values and the same trend of the above three indexes could be observed in MAFLD and liver fibrosis. Subgroups analyses showed consistent results with the primary research, despite some heterogeneity. Conclusions: TyG-WC, TyG-WHtR and TyG-BMI can be used for early screening of NAFLD and MAFLD. These three parameters and HOMA-IR were more suitable for assessing metabolic risks and monitoring disease progression in patients with NAFLD.